Leishmania spp.-Infected Dogs Have Circulating Anti-Skeletal Muscle Autoantibodies Recognizing SERCA1 - Prisco, Francesco (Pathogens, 2021)
Leishmania spp. infection is associated with an inflammatory myopathy (IM) in dogs. The pathomechanism underlying this disorder is still elusive, however, the pattern of cellular infiltration and MHC I and II upregulation indicate an immune-mediated myositis. This study aimed to investigate the presence of autoantibodies targeting the skeletal muscle in sera of leishmania-infected dogs and individuate the major autoantigen. We tested sera from 35 leishmania-infected dogs and sera from 10 negative controls for the presence of circulating autoantibodies with indirect immunofluorescence. Immunoblot and mass spectrometry were used to identify the main target autoantigen. Immunocolocalization and immunoblot on immunoprecipitated muscle proteins were performed to confirm the individuated major autoantigen. We identified circulating autoantibodies that recognize skeletal muscle antigen(s) in sera of leishmania-infected dogs. The major antigen was identified as the sarcoplasmic/endoplasmic reticulum Ca(2+)-ATPase 1 (SERCA1). We also found that canine SERCA1 presents several identical traits to the calcium-translocating P-type ATPase of Leishmania infantum. In the present study, we defined circulating anti-SERCA1 autoantibodies as part of the pathogenesis of the leishmania-associated IM in dogs. Based on our data, we hypothesize that antigen mimicry is the mechanism underlying the production of these autoantibodies in leishmania-infected dogs.